Effect of Fibrozyme® on degradability and degradation kinetics of chickpea straw (Cicer arietinum) - López-Inzunza, Hugo de Jesús; Chongo-García, Bertha Bienvenida; La-O-León, Orestes; Guerra-Liera, Juan Eulogio; López-López, Hugo; Luna-López, Maribel; López-Juárez, Luciano Abelino; Castro-Camacho, Samuel Jesús (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This research aimed at studying the effect of a complex of exogenous fibrolytic enzymes (Fibrozyme®) on the in situ ruminal degradability parameters and degradation kinetics of dry matter (DM) of the chickpea (Cicer arietinum) straw. For the experiment, we used two cannulated Swiss bulls (700 kg PV), in a randomized block design, where each animal represented a block. We evaluated three enzyme levels (0, 1, and 2 g Fibrozyme® kg forage−1 DM), and put nailon bags at five different incubation times (6, 12, 24, 48, and 72 h). The results showed that including 2 g of Fibrozyme® kg-1 DM improves in situ digestibility of dry matter of chickpea straw (P<0.05) for all incubation times, as well as the degradation kinetics parameters. We conclude that 2 g kg-1 forage DM of the studied Fibrozyme® improves the in situ degradation kinetics and ruminal degradability of DM of the evaluated farm residue.